Examining the Correlation between Family Environment and Cognitive Learning Outcomes in Pancasila Education among Elementary School Students in Jakarta - Aulia Putry; Otib Satibi Hidayat; Nidya Chandra Muji Utami (MASI Mandiri Edukasi, 2025)
This study investigates the correlation between family environment and the cognitive learning outcomes of fifth-grade students in Pancasila Education at public elementary schools in the Joglo Administrative Village, West Jakarta. The study adopts a quantitative correlational design with a sample of 87 students selected through simple random sampling. Data were collected using a family environment questionnaire and a cognitive test on the topic of Norms, both of which were validated and found reliable (Cronbach’s α = 0.836). The data were analyzed using the Pearson Product-Moment correlation test, preceded by normality and linearity checks. Results revealed a strong positive correlation (r = 0.663, p < 0.05) between family environment and students’ cognitive learning outcomes. The determinant coefficient (R² = 0.44) indicates that the family environment accounts for 44% of the variance in learning outcomes, with the remaining 56% attributed to other factors, such as school context, peers, and motivation. These findings affirm the significant role of family support, attention, and parenting patterns in shaping students’ academic performance, particularly in subjects related to moral and civic education, such as Pancasila Education. The study recommends enhanced collaboration between schools and parents to improve student achievement through a supportive learning environment.